Utility and Usefulness of the Skills Laboratory to Improve Practical Training in Clinical Skills - MIYAZAKI, Hiroshi; HAYASHI, Akihiro; TAKAJYO, Yoshinori; USHIJIMA, Kimio; UENO, Takato; SATA, Michio; KUROKI, Taketo; SUEYASU, Yoshiko; TORIMURA, Takuji; YOSHIMURA, Kouichi; KONO, Syusuke; WATANABE, Masayuki; et al. (Igaku Kyoiku / Medical Education (Japan), 2003)
Medical students at Kurume University begin practical training in clinical skills in their fourth year. At that time, students use the skills laboratory to improve their clinical skills. Medical education resources in the skills laboratory include simulators for emergency resuscitation and heart diseases, wireless stethoscopes, and videotapes. All students use the skills laboratory for 2 months, and its usefulness was evaluated with questionnaires after practical training. More than 50 % of students approved of their practice in the skills laboratory. However, some students were unsatisfied because they were unable to make effective use of the simulators. In the future, an improved skills laboratory will be necessary to improve practical training in the clinical skills for medical students.